Climbing a Cocoanut [sic] Tree, Trinidad - (:unkn) unknown (My University, 2009)
A picture of a man climbing a coconut tree using a rope to assist.
Colour: Black and White; Style: Portrait; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Coconut palm--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Male blue collar workers--Trinidad and Tobago; Tree climbing--Trinidad and Tobago